Needs, Challenges, and Opportunities in Establishing and Maintaining Medical Education in Karnali Academy of Health Sciences (KAHS) - Regmi, Kiran; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2019)
The constitution of Nepal (2015), article 35 (Right relating to health) stated that every citizen shall have the right to free basic health services from the State, and no one shall be deprived of emergency health services. According to the World Bank report (collection of development indicators compiled from various official sources, 2016), Nepal has 81% rural and remote populations. Health service delivery is a complex reality for the rural and remote populations and faces enormous challenges. One of them is insufficient and uneven distribution of health workforce. The World Health Report concluded that "the severity of the health workforce crisis is in some of the world's poorest countries, of which 6 are in South East Asia out of 57 countries having critical shortages of health workforce."1Even after 13 years situation has not much improved. Nepal faces a critical shortage of trained health workforce, especially in rural and remote areas. Health workforce recruitment and retention in rural and remote areas is a difficult task challenged by the preferences and migration of health workforce to urban areas in country, or even abroad for better life and professional development.2 One of the most effective strategies for health workforce recruitment and retention for rural and remote areas could be that of establishing and maintaining Medical Education in rural and remote areas decentralized from urban academic medical centers.